Integrated Assessment of Oxidative Stress, Inflammatory Biomarkers, and Gastrointestinal Motility Dysfunction in Patients with Non-Alcoholic Fatty Liver Disease (NAFLD) - Hashmat Ullah Khan, Sheema Khan, Zainab Fakhar Ul Qammer, Tariq Hussain, Syma Arshad, Rao Salman Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is a growing metabolic disorder with systemic implications beyond the liver. Oxidative stress and low-grade inflammation are pivotal in its pathogenesis, but their association with gastrointestinal (GI) motility disturbances remains underexplored. Objective: To evaluate oxidative stress markers, pro-inflammatory cytokines, and their correlation with gastrointestinal motility parameters in patients with NAFLD. Methods: This cross-sectional study was conducted in the Department of Medicine, Lady Reading Hospital MTI, Peshawar, from May 2022 to May 2023. Ninety adult patients diagnosed with NAFLD via ultrasonography were included. Oxidative stress was assessed by measuring serum malondialdehyde (MDA) and reduced glutathione (GSH). Inflammatory markers, including TNF-α, IL-6, and IL-1β, were quantified using ELISA. Gastric emptying time was evaluated by radionuclide scintigraphy, while colonic transit time was assessed using the radiopaque marker method. Correlation analyses were conducted using Pearson's coefficient. Results: NAFLD patients exhibited significantly elevated MDA (6.87 ± 1.52 nmol/mL) and inflammatory markers, with reduced GSH levels (2.03 ± 0.61 µmol/g protein). Gastric emptying time (99.56 ± 13.71 min) and colonic transit time (59.73 ± 8.62 h) were significantly delayed. Strong positive correlations were found between TNF-α and GI motility delays (r > 0.67, p < 0.001), while GSH showed inverse associations. Conclusion: Patients with NAFLD experience significant oxidative stress, inflammation, and gastrointestinal motility impairment. These systemic abnormalities are interlinked and may serve as predictive markers for subclinical GI dysfunction. Integrating biochemical and motility assessments may enhance comprehensive care in NAFLD. Keywords: NAFLD, oxidative stress, gastrointestinal motility, inflammation, TNF-α, glutathione